Tinjauan Yuridis Terhadap Efek Bersifat Utang Berwawasan Lingkungan (Green Bond) Sebagai Instrumen Investasi Dalam Penerapan Sustainable Investment Di Pasar Modal Indonesia - Josua L. Tobing, Kevin Sebastian; Setiawati, Wenny (UI Scholars Hub, 2022)
Global attention to the climate change issues has significantly increasing. The manifestation of the increasing international awareness of the climate change’s threat was engraved in the Paris Agreement and Sustainable Development Goals Agenda by United Nations. These two agreements have created a universal term of reference for the concept of sustainable investment globally acknowledged. The concept of sustainable investment itself was developed from the shifting from values based investing approach into investment approach which based on sustainability principle and the integration of environmental, social, and governance factors. The development of sustainable investment on the fixed income assets classes has created a new instrument for investing that called green bond. For the purpose to issuing a green bond, every nations including Indonesia, have a different characteristic of regulation different from others. However, Indonesia have problems in implementing green bond: regarding the low risk assessment and credit rating from international institution for Indonesia’s private corporation. These problems created difficulties for Indonesian corporation in finding foreign investors which are willing to invest in the green bond issued by them. Nevertheless, there is potential sources of allocating sustainable investment to fund green bond through regulated environmental funding instrument. This article will discuss on the implementation of green bond in Indonesia, and its position as an environmental funding instrument, hence exercising the sustainable investment principles.